From the Editor on recent recommendations on women’s health, pregnancy, and the offspring - Pacheco-Romero, José (2019)
New research in our specialty is complex and exciting, and it is in our interest to share some of it to stimulate research in our countries and institutions. We start the presentation with brief summaries related to women’s health.